Experimental and numerical investigation on friction drilling of difficult-to-machine materials - Dehghan, Shayan (2019)
Friction drilling is a non-conventional hole-making process that utilizes a rotating conical drilling tool to penetrate workpiece and create a hole by forming a bushing without generating chip. In metallurgy, difficult-to-machine materials are defined as materials which have great toughness, high work-hardening and low thermal conductivity. Since the difficult-to-machine materials are receiving increasing attention in extreme applications, friction drilling offers a great potential for product fabrication. However, the major challenge of friction drilling on difficult-to-machine materials is the difficulty of machining that leads to poor friction drilling performance and short tool life. In this study, the friction drilling on difficult-to-machine materials of stainless steel AISI304, titanium alloy Ti-6Al-4V and nickel-based alloy Inconel718 using drilling tool of tungsten carbide was experimentally and numerically investigated. Experimental results revealed that the thermal and mechanical properties of work-materials, spindle speed and feed rate have great influence on the formation of bushing and tool life. To achieve maximum number of acceptable drilled-holes, the optimum process parameters for AISI304 are spindle speed 1000 rpm and feed rate 105 mm/min, for Ti-6Al- 4V are spindle speed 1000 rpm and feed rate 145 mm/min, and for Inconel718 are spindle speed 1500 rpm and feed rate 145 mm/min. The maximum frictional heating is generated at bushing completion stage, where the conical region of drilling tool is contacted to drilled hole-wall. The higher thrust force was occurred in initial contact between drilling tool and workpiece, and consequently the circular grooves and work-material adhesion have proven that abrasive and adhesive wear occurred on center and conical regions of drilling tool, respectively. The maximum abrasive wear, adhesive wear and oxidative wear are occurred on drilling tools which drilled AISI304, Ti-6Al-4V and Inconel718, respectively. The developed numerical model can well represent the real process of friction drilling, and stress and temperature distributions on workpiece and drilling tool. It also can effectively demonstrate the heating distribution on workpiece, material softening and bushing formation. The numerical results indicated that severe stress occurs at the tool contact surface and adjacent region in the initial penetration. The inverse relationship between stress and temperature demonstrate the phenomenon of frictional heating and softening of the work-material in friction drilling which forms the bushing. Furthermore, the high plastic strain occurs on the hole-wall, which is the contact surface between drilling tool and work-material and it depends on the tool movement along the drilling path. The main contribution of this study is determining the effect of process parameters on drilling tool performance, bushing formation quality, thrust force and tool wear for friction drilling of difficult-to-machine materials with approach to improve friction drilling performance and reduce tool wear. Moreover the developed finite element modeling can provide a prediction for friction drilling process. In overall, this work demonstrated the behaviors of chip-less friction drilling on difficult-to-machine materials that can offer a great potential for a new product design and manufacturing.